Statics and Dynamics of Twisted Skyrmion Tubes in Frustrated Magnets - Saavedra-Díaz, E (American Physical Society, 2025)
Stable three-dimensional topological skyrmion structures in frustrated magnets are investigated. The texture exhibits a helicoid pattern along the vertical direction, described by a position-dependent helicity, which interpolates between Neel-and hedgehoglike two-dimensional skyrmions, characterized by the Hopf index, and is referred to as "twisted skyrmion tubes" (TSkTs). The stability and topology of TSkTs are achieved by competing next-nearest-neighbor exchange interactions, the thickness of the magnet, and the applied magnetic field. The dynamical behavior of a twisted structure in frustrated magnets is determined. Specifically, we derive that the helicity dynamics of the TSkT can be driven by an electric current resulting from spin-orbit torque interaction. Furthermore, we address the study of the electronic scattering problem using a spin-orbit-torque-driven TSKT, which offers promising applications for low-power storage nanodevices and nanobatteries with enhanced control.